2020
DOI: 10.1021/acsami.0c09973
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrashort Peptide-Based Supramolecular Hydrogel Mimicking IGF-1 to Alleviate Glucocorticoid-Induced Sarcopenia

Abstract: Sarcopenia is a common disease in older people due to aging, and it can also occur in midlife because of diseases including cancer. Sarcopenia, characterized by rapid loss of muscle mass and accelerated loss of function, can lead to adverse outcomes such as frailty, falls, and even mortality. The development of pharmacological and therapeutic approaches to treat sarcopenia remains challenging. The growth status and quantity of myoblasts are the key factors directly affecting muscle formation. Therefore, enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…A recent study confirmed that resistance interval training (RIT) and resistance aerobic exercise (RAE) can effectively improve physical health and sleep quality by increasing the area of skeletal muscle and IGF-1 in elderly women ( Yoon et al, 2019 ). A supramolecular nanofiber/hydrogel formed by Nap-FFGSSSR mimics IGF-1 and can increase the phosphorylation of Akt by activating the insulin-mediated signaling pathway, which effectively promotes the proliferation of myoblasts, significantly reduces the apoptosis of myoblasts induced by dexamethasone, helps the myoblasts to differentiate into myotubes, and prevents the fibrosis of muscle tissue and the deposition of collagen;( Shang et al, 2020 ) these results show a prominent effect of IGF-1 in the treatment of sarcopenia. The expression of the full propeptide IGF-1Ea of IGF-1 promotes a significant hypertrophic phenotype in young mice and maintains this phenotype in older mice.…”
Section: Bone-muscle Biochemical Crosstalkmentioning
confidence: 82%
“…A recent study confirmed that resistance interval training (RIT) and resistance aerobic exercise (RAE) can effectively improve physical health and sleep quality by increasing the area of skeletal muscle and IGF-1 in elderly women ( Yoon et al, 2019 ). A supramolecular nanofiber/hydrogel formed by Nap-FFGSSSR mimics IGF-1 and can increase the phosphorylation of Akt by activating the insulin-mediated signaling pathway, which effectively promotes the proliferation of myoblasts, significantly reduces the apoptosis of myoblasts induced by dexamethasone, helps the myoblasts to differentiate into myotubes, and prevents the fibrosis of muscle tissue and the deposition of collagen;( Shang et al, 2020 ) these results show a prominent effect of IGF-1 in the treatment of sarcopenia. The expression of the full propeptide IGF-1Ea of IGF-1 promotes a significant hypertrophic phenotype in young mice and maintains this phenotype in older mice.…”
Section: Bone-muscle Biochemical Crosstalkmentioning
confidence: 82%
“…However, the effects may vary in different cell types and disease conditions. IGF-1bsn has been shown to inhibit a variety of disorders, including ischemic limb disease, sarcopenia, acute kidney injury, and atherosclerosis [ 40 , 42 , 68 , 69 ]. However, to the best of our knowledge this study is the first to report the positive effect of IGF-1 bsn on gap integration after mosaicplasty in osteochondral defect therapy.…”
Section: Discussionmentioning
confidence: 99%
“…8C and D show that assemblies of 37 reduce the myoblast damage in a dexamethasone (Dex)-instructed sarcopenia model. 98 Additionally, as shown in Fig. 8E , 38 , an amphiphile molecule similar to 35 but having d -formed amino acids, self-assembles to form a hydrogel.…”
Section: Sasms For Maintaining Physiological Functions Of Normal Cellsmentioning
confidence: 95%
“… 97 Encouraged by this study, other SASMs, which also mimic IGF-1, are capable of treating other diseases, such as treating sarcopenia and AKI. 98,99 As shown in Fig. 8B , an ultrashort sequence SSSR substitutes IGF-1C in 35 , forming compound 37 .…”
Section: Sasms For Maintaining Physiological Functions Of Normal Cellsmentioning
confidence: 97%